FENOMENA SELF HEALING UNTUK PENGHILANG STRES SEBAGAI PROMOSI PARIWISATA MELALUI DESTINASI HIDDEN GEM JUNGGLE MILK LEMBANG - Superwiratni, Superwiratni; Yayan Sugiarto (Bajang Institute, 2024)
Selft Healing itself is currently used by young people to get out of the fatigue of the mind, daily problems from the pile of tasks and work problems to go on a trip abroad, to the shopping center, to the streets, to the beach, to the mountains or just to eat at a restaurant with a soothing view or to go to places called hidden gems to find calm. In this study, there is more focus on, first,